The rational design of bifunctional MOF-ZnFe2O4 hollow sphere-based nanocomposites for ultra-efficient electrochemical oxygen evolution reaction and high-performance symmetric supercapacitor electrodes - Lee D.-E.; Danish M.; Husain A.; Jo W.-K. (Elsevier Ltd, 2025)
Supercapacitors have emerged as versatile energy storage devices, valued for their rapid charge-discharge capabilities and long cycle life. Concurrently, efficient electrocatalysts are essential for promoting the oxygen evolution reaction (OER) in sustainable energy applications. Inevitably, this study explores the integration of a Cobalt-Nickel (Co/Ni) based metal-organic framework [CoNi((?3-tp)2(?2-py)2 or CNTP] with ZnFe2O4 hollow spheres (ZHS) to create innovative CNTP/ZHS nanocomposites tailored for supercapacitor and electrocatalytic OER applications. Different weight percentages of CNTP/ZHS nanocomposites were synthesized through a facile and scalable method, and their electrochemical performance was rigorously assessed. Electrochemical characterization revealed that a 40 wt percentage CNTP/ZHS (40-CNTP/ZHS) electrode demonstrated a very high specific capacitance of 1519.2 Fg?1 at 1 Ag?1 and retained 92.6 % of its specific capacitance after 10000 cycles. Moreover, it delivered remarkably high specific capacitance (447.2 Fg?1) and energy density (62.1 WhKg?1) along with outstanding cyclic stability (97.5 % after 5000 galvanostatic charge-discharge cycles). It also exhibited excellent OER activity, with a very low overpotential (207 mV to attain a current density of 10 mAcm?2), a small Tafel slope (66.5 mVdec?1), and high stability over 2000 cyclic voltammetry cycles. These characteristics underscore the significant potential of renewable energy technologies, particularly for water electrolysis and sustainable energy conversion.1 ? 2024 Elsevier B.V.